Linking Research to Global Health Equity: The Contribution of Product Development Partnerships to Access to Medicines and Research Capacity Building - Pratt, Bridget (American Public Health Association, 2013)
Certain product development partnerships (PDPs) recognize that to promote the reduction of global health disparities they must create access to their products and strengthen research capacity in developing countries. We evaluated the contribution of 3 PDPs—Medicines for Malaria Venture, Drugs for Neglected Diseases Initiative, and Institute for One World Health—according to Frost and Reich’s access framework. We also evaluated PDPs’ capacity building in low- and middle-income countries at the individual, institutional, and system levels. We found that these PDPs advance public health by ensuring their products’ registration, distribution, and adoption into national treatment policies in disease-endemic countries. Nonetheless, ensuring broad, equitable access for these populations—high distribution coverage; affordability, particularly for the poor; and adoption at provider and end-user levels—remains a challenge.